2013
DOI: 10.2106/jbjs.l.00552
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Glenoid Component in Anatomic Total Shoulder Arthroplasty

Abstract: This is the first systematic review of the published evidence on glenoid component failure. Although the authors of individual articles proposed various risk factors for glenoid component failure, many of these relationships were not significant in the present study. A consistent methodological approach to future investigations is likely to improve the quality of the evidence on which patients, techniques, and prostheses are selected for total shoulder arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(39 citation statements)
references
References 36 publications
1
37
1
Order By: Relevance
“…Subsequent symptomatic glenoid component loosening and component revision occurred at 1.2 and 0.8 % per year, respectively [32]. Metal-backed glenoid components have higher complications compared to all polyethylene components, consequently cemented all-polyethelene components have become the implant of choice for most surgeons [31,32]. Revision shoulder arthroplasty universally leads to poorer outcomes when compared to the outcomes after a primary anatomic total shoulder arthroplasty, emphasizing the importance of getting the glenoid component correct at the primary surgical procedure [31,33].…”
Section: Common Failure Mechanisms Of and Difficulties In Shoulder Armentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent symptomatic glenoid component loosening and component revision occurred at 1.2 and 0.8 % per year, respectively [32]. Metal-backed glenoid components have higher complications compared to all polyethylene components, consequently cemented all-polyethelene components have become the implant of choice for most surgeons [31,32]. Revision shoulder arthroplasty universally leads to poorer outcomes when compared to the outcomes after a primary anatomic total shoulder arthroplasty, emphasizing the importance of getting the glenoid component correct at the primary surgical procedure [31,33].…”
Section: Common Failure Mechanisms Of and Difficulties In Shoulder Armentioning
confidence: 99%
“…In anatomic total shoulder arthroplasty, the glenoid component accounts for 24 % of all complications [31]. In addition, a recent systematic review demonstrated that asymptomatic radiolucent lines appeared at a rate of 7.3 % per year after primary TSA [32]. Subsequent symptomatic glenoid component loosening and component revision occurred at 1.2 and 0.8 % per year, respectively [32].…”
Section: Common Failure Mechanisms Of and Difficulties In Shoulder Armentioning
confidence: 99%
See 1 more Smart Citation
“…However, symptomatic loosening and surgical revision occurred at roughly 1 % per year [23]. The most common reason for failure and revision of total shoulder replacement is failure of the glenoid component [18].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic glenoid loosening is seen at a rate of 1.2% per year, and surgical revision at 0.8% per year. 17 The risk ratio for revision of radiolucent lines amounts 0.27, with a higher risk for keeled than for pegged components. 23 Moreover, metal-backed prostheses have a higher rate of failure than all-polyethylene components.…”
mentioning
confidence: 99%